2008
DOI: 10.1121/1.2934071
|View full text |Cite
|
Sign up to set email alerts
|

SOUND-SCAPE: A framework for characterising positive urban soundscapes

Abstract: In order to inform the planning process with regard to assessing and creating positive urban soundscapes, a framework is under development. The framework attempts to bring together all the influencing factors in urban soundscape assessment in a new and novel way, and considers how the identification of sources and the variety and mix of sources interact to produce a soundscape. The framework presented in this paper forms the basis of multidisciplinary soundscape research in the EPSRC funded "Positive Soundscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 2 publications
2
15
0
1
Order By: Relevance
“…Managing the Warsaw soundscape must be executed in parallel with decreasing sound level. When sound level is low enough, then many other factors have a huge impact on perception of the soundscape (Cain et al 2008). This is in accordance with Lewandowski & Szumacher (2008), who conducted surveys to find out which places, evaluated as having the same sound level, have different pleasantness ratings.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Managing the Warsaw soundscape must be executed in parallel with decreasing sound level. When sound level is low enough, then many other factors have a huge impact on perception of the soundscape (Cain et al 2008). This is in accordance with Lewandowski & Szumacher (2008), who conducted surveys to find out which places, evaluated as having the same sound level, have different pleasantness ratings.…”
Section: Discussionsupporting
confidence: 58%
“…Zhang & Kang (2007) claim that under a certain level of sound pressure, human perception of soundscape quality does not correlate with loudness. Cain et al (2008) created four categories of factors affecting the perception of soundscapes:…”
Section: Miscellanea Geographica -Regional Studies On Developmentmentioning
confidence: 99%
“…More significantly age plays a greater role in sound perception. The same study showed that younger people (10)(11)(12)(13)(14)(15)(16)(17) year olds) are less tolerant of sounds relating to nature whereas older people are more likely to prefer soundscapes where natural sounds occur. In a similar study by the same authors [9], cultural background and environmental experience play an important role in people's judgement of sound preference.…”
Section: Introductionmentioning
confidence: 76%
“…Cain et al [11] propose that it is the contextual issues faced by the listener which will influence the perception of a given soundscape and is based on an activity-centric standpoint i.e. who you are, why and how you are listening, the time of day, and the location and type of space you are in.…”
Section: Introductionmentioning
confidence: 99%
“…This diffuses a legislative rather than a design intention throughout soundscapes. As has been described by a number of soundscape practitioners, most recently within Britain's Positive Soundscape Project (PSP) [23] this focuses attention on the negative impacts of sound, while ignoring the potentially positive aspects of sound. In response there has been a growing awareness for the need of intentionally designed soundscapes that have a positive effect on listener perception and human health.…”
Section: Differentiating Incidental and Intentional Soundscapesmentioning
confidence: 99%